2014
DOI: 10.5194/nhess-14-2009-2014
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the WRF model to the lower boundary in an extreme precipitation event – Madeira island case study

Abstract: Abstract. The advances in satellite technology in recent years have made feasible the acquisition of high-resolution information on the Earth's surface. Examples of such information include elevation and land use, which have become more detailed. Including this information in numerical atmospheric models can improve their results in simulating lower boundary forced events, by providing detailed information on their characteristics. Consequently, this work aims to study the sensitivity of the weather research a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
(52 reference statements)
3
16
0
Order By: Relevance
“…Aside from under-resolved terrain height in modeled grids, which is essentially an oversimplification of the source terrain height data, we show in this paper that uncertainty in source terrain height data sets themselves can be significant enough to result in fundamental differences in simulated orographic flow mechanics. This finding illustrates that the sensitivity of NWP models can be more complex than first-order biases recently documented by Teixeira et al (2014).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Aside from under-resolved terrain height in modeled grids, which is essentially an oversimplification of the source terrain height data, we show in this paper that uncertainty in source terrain height data sets themselves can be significant enough to result in fundamental differences in simulated orographic flow mechanics. This finding illustrates that the sensitivity of NWP models can be more complex than first-order biases recently documented by Teixeira et al (2014).…”
Section: Introductionsupporting
confidence: 64%
“…The windward islands of the LA are generally lower than GC but are, nonetheless, predominately mountainous with peak elevations near 1 km for each island (see Table 1). The corresponding near-surface wind retrievals from the ASCAT (Advanced Scatterometer) instrument (Vogelzang et al, 2011) on the MetOp-B (Meteorological Operational) satellite are shown in Fig. 2 (right panel).…”
Section: Case Studies and Modeling Detailsmentioning
confidence: 99%
“…In recent years, WRF has been widely used in both academic research and industry [32][33][34]. Many studies show that WRF can simulate lower boundary conditions well over complex orography [35,36], which can help WRF to couple with CFD accurately.…”
Section: Wrf Model Setupmentioning
confidence: 99%
“…To solve this problem, meteorological models can be applied in a grid with very high resolution (horizontal grid spacing around 1 km), and physiographic high resolution data may be introduced in the model, allowing incorporating the physical characteristics of the region with greater accuracy and representativeness. In this sense, numerous studies have demonstrated how the incorporation of topography [8]- [12] and land uses [13]- [15] databases with higher resolution significantly improve the forecast performance. Topography and land cover influence on wind patterns, land surface atmosphere interactions, such as low level turbulence and transport, convection, precipitation, runoff, etc.…”
Section: Introductionmentioning
confidence: 99%